Technical Analysis Applied in the Inspection of Distress on the Surface of Asphalt Pavement using Remotely Piloted Aircraft (RPA) - Vieira Barbalho, Leonardo; Lopes Guerra Neto, Hélio; Oda, Sandra; Antoun Netto, Sergio Orlando (Anuário do Instituto de Geociências, 2025)
The transport sector can be considered one of the most important in promoting urban mobility in Brazil. The lack of efficient road planning and transport greatly affects people's daily journeys. Another important factor is the increase in the number of vehicles in Brazilian municipalities, which also contributes to the negative outlook regarding traffic in Brazil. This work aimed to use Remotely Piloted Aircraft (RPA) to obtain images that enable analyzes of the surface conditions of the asphalt pavement. The place where the study was carried out was the BRT TransOeste corridor in Rio de Janeiro, which connects the Barra da Tijuca region to Santa Cruz and Campo Grande, passing through Guaratiba and Recreio dos Bandeirantes. The following procedures were adopted: flight planning with RPA, observing the Ground Sample Distance (GSD) recommended by scientific literature, field support using Global Navigation Satellite System (GNSS) Networked Transport of Radio Technical Committee for Maritime Service (RTCM) via Internet Protocol (NTRIP) technology, processing of images obtained using Agisoft software, generation of orthophoto orthorectified and assessment of distress on the asphalt surface based on the analysis of images obtained with RPA using the Pavement Condition Index (PCI).